PEMBERDAYAAN NILAI-NILAI INSTITUSI DAN HOLISTIC EDUCATION Kajian Kontribusi Pemimpin Pendidikan terhadap Gerakan Revolusi Mental - Kholid Junaidi (MUADDIB Jurnal Kependidikan dan Keislaman, 2017)
Mental revolution movement in Indonesia is based on the phenomena of mental negative development in many different ages and other fields such as corruption, drugs, murder, robbery, thievery, prostitution, violence, gambling and sexual insulting. The development of mental negative in society is reputed as the implementation product that only produces the change of cognitive product in low level (knowing and comprehending) and it has not reached the high level of cognitive product (analyzing, synthetic, and evaluating). Education institution as the main tool and also as the first builder of mental Indonesian should be able to optimize all of intellectual potentials, emotions, social physic, aesthetic, and spirituality as comprehensive as balanced (holistic education) so that it can create the real human. In this case, it is needed more professional education management to empower the environment and also spiritual values as source of study; and to develop communication and cooperation with formal, non formal and informal institutions.As the leader of education institution, headmaster should be more serious in doing socialization, comprehension, and fulfillment the quality of the components in implementing the real education such as competent human resources, education curriculum, supporting facility and also empowering the cultural values of institution. Teachers as agents of mental revolution should increase their competences especially in using curriculum in various, fun, democratic and meaningful teaching-learning process so that it can be built the characters and positive attitudes of students. Commitment and cooperation among headmaster, teachers, society and government in building positive values will make faster to create Indonesian that are cultured as the goal of the mental revolution movement